Estudo da dinâmica da frequência cardíaca do repouso ao exercício físico em pacientes com doença arterial coronariana - Neves, Victor Ribeiro (2011)
The study of heart rate variability (HRV) has been used to assess the cardiac autonomic control in different population both on the supine position and during exercise test. The reduction of cardiac autonomic control has been observed in coronary artery disease (CAD) patients, since the progression of CAD to acute myocardial infarction (AMI) can be related with symphatovagal imbalance. The HRV has been traditionally assessed by linear methods, but in recent years, the use of some nonlinear methods has provided additional data, which does not uncovered by linear analysis. Thereby, the first study had the aim to compare the HRV of CAD patients with and without AMI (CAD-AMI) with health-matched controls by linear (spectral analysis) and nonlinear (Shannon entropy, conditional entropy and symbolic analysis). Fifty-six men were divided into three groups: healthy (n=19, 57±4 years), CAD (n=20, 56±10 years) and CAD-AMI (n=19, 54±12 years). There was no difference between the groups regarding cardiac autonomic modulation by linear (spectral analysis) and nonlinear (Shannon entropy, conditional entropy and symbolic analysis). These results may be due to beta-blocker use, coronary angioplasty, exercise capacity of healthy subjects and methodology this study. Thereby, in studied conditions, methods of analysis used showed no difference in cardiac modulation between groups. On the other hand, CAD can be to take together type 2 diabetes (T2D), which is a disease that worsens the impairment of cardiac autonomic modulation. Other method used in this study, is assessment the behavior of hear rate response and variability in the phase recovery after physical exercise. Therefore, the incidence of cardiovascular events is higher in CAD patients with type 2 diabetes (CAD+T2D) than in CAD patients without T2D. There is increasing evidence that the recovery phase after exercise is a vulnerable phase for various cardiovascular events. However, the second study had the aim to assess the autonomic regulation of CAD patients with and without T2D during post-exercise condition. One-hundred-two patients were divided into two groups: CAD (n=68, 61±5 years) e DAC+DT2 (n=64, 62±5 years), which underwent cardiopulmonary exercise testing. The result of second study indicated that DAC+T2D patients had a higher delay of heart rate recovery in comparison with DAC patients without T2D. However, there no differences between the groups in heart rate recovery after adjustment for exercise capacity, body mass index and medications. Thereby, the result of this second study suggesting impairment of cardiac autonomic control after exercise in diabetic patients compared x with non-diabetic patients is more closely related to low exercise capacity and obesity than to T2D itself.